Re-Explaining the Urgency of the Death Penalty in Realizing a Deterrent Effect in Cases of Premeditated Murder - Ansari, Muhammad (Jurnal Daulat Hukum, 2024)
One of the extraordinary crimes in this country is premeditated murder, this is because premeditated murder is carried out with evil planning consciously and thinking in advance, where the result of this crime is the loss of a person's life. The death penalty in suppressing the number of premeditated murder cases through efforts to create a deterrent effect with fear of the death penalty needs to be re-examined legally, because the element of planning is difficult to interpret in premeditated murder, and there are fundamental changes in the imposition of the death penalty for perpetrators of premeditated murder has become an obstacle in itself in the implementation of the death penalty as a penal medium in creating a deterrent effect for perpetrators of premeditated murder. This article with a normative method tries to discuss the death penalty as a means of creating a deterrent effect for perpetrators of murder both in the aspect of normative studies and in comparative legal studies in the scope of the comparison between the death penalty according to the old Criminal Code and the new Criminal Code. So this article intends to describe the development of the death penalty system for perpetrators of premeditated murder according to the development of the National Criminal Code. Based on the existing study, it can be seen that the death penalty in preventing the increase in premeditated murder in society is currently not optimal, the cause is the difficulty in understanding the meaning of planning due to not being written down in the Criminal Code what is meant by planning in premeditated murder. The second problem is the change in the criminal threat for perpetrators of premeditated murder in Article 459 of the Republic of Indonesia Law No. 1 of 2023 concerning the Criminal Code, where the presence of this provision creates a loophole for perpetrators of premeditated murder to avoid the death penalty due to the minimum sentence of 20 years in prison. In addition, the change in the position of the death penalty to an alternative sentence with conditions also opens up a loophole for perpetrators of premeditated murder to be free from the death penalty.